Praktik Perkawinan Sapowik (Study Kasus di Desa Tanjung) Dalam Tinjauan Hukum Islam - Mustafid,; Satri Muliadi,; Ahmad Iffan, (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2022)
This paper wants to describe the implementation of the Sapowik marriage in the village of Tanjung and also how Islamic law views on this Sapowik marriage. The method used in this research is a qualitative approach, the type of field research. After analyzing this research, it concludes that the ban on Sapowik marriages is still in effect today, of course, there will be customary sanctions for those who violate it. Then from the point of view of Islamic law, these customs are contradictory. Then when viewed from the theory of 'Urf, the prohibition of Sapowik's marriage is included in 'Urf Fasid, theoretically, Ushul Fiqh Sad Al-Dzariah, the prohibition of Sapowik's marriage is unacceptable because many mafsadah will appear.